Metal fused filament fabrication (MF3) of Ti-6Al-4 V implants by using flexible, partially water-soluble binder systems - Ralf Eickhoff; Steffen Antusch; Dorit Nötzel; Thomas Hanemann (Materials & Design)
Metal Fused Filament Fabrication provides a cost-efficient method to produce metal implants adapted to the patient. However, the limited flexibility of highly filled filaments and the reduced accuracy in comparison with alternative additive manufacturing techniques currently restrict the widespread implementation of this method. Building upon the findings of previous studies, the eco-friendly partially water-soluble binder systems containing polyethylene glycol (PEG), poly(vinylbutyral) (PVB) and poly(methylmethacrylat) (PMMA) were further optimized. Consequently, the influence of the plasticizer acetyltributylcitrate (ATBC) on the flow behavior and the flexibility of the filaments was investigated. The combination of all binder components, in conjunction with a solids content of 60 %, has enabled the fabrication of filaments with a high degree of usability, attributable to their remarkable flexibility and excellent printing properties. Following the debinding and sintering processes, the manufacturing of implants with densities that exceed 99.5 % of the theoretical values was feasible.